A system study on the Warehousing Department of Zeno Chemical Industries, Inc. - De Guzman, Diego Lorenzo B. (Animo Repository, 2023)
Zeno Chemical Industries, Inc. is a company that imports and distributes chemical raw materials to several branches of pharmaceutical and/or veterinary industries. Prior to it being the company that it is today, it originally operated as a small local trading company named Zeno Marketing in 1989, wherein chemical raw materials were originally bought from local suppliers instead of foreign ones. The company was handled by two people, Zenaida Agustin (founder), and her documentation assistant, while residing in a 25 square meter office warehouse located at Makati City, Philippines. By 1997, Zeno Marketing expanded its number of employees and eventually started buying from foreign suppliers. The company was later renamed Zeno Chemicals Industrial, Inc. to better establish itself as a rising chemical company. It was through this that the company widened its operations and relocated to a 2,000 m2 office complex in Taytay, Rizal during 2011. At present, Zeno continues to act as a leading importer and distributor of chemical raw materials for pharmaceutical and/or veterinary industries in the Philippines. With the assistance of the company representatives, a thorough review of the company’s processes, financial statements, inventory checklists, and documentation were done in order to determine any present problems. Numerous possible problems were found through a SWOT analysis. A ranking for each weakness found was determined by the use of a WOT-SUG analysis. The analysis gives a numerical rank per problem found and helps give prioritization to the problem with the largest numerical figure. It was found that the average product returns in kilos per month was deviated by 0.42% from Zeno Chemical Industries Inc,’s maximum tolerable limit of 0.01% during the time period of Aug 2021 to Aug 2022 which has resulted in a monthly cost of 10,731 PHP. As the main problem is found, the next concern is pinpointing the possible causes to the main problem. The Why-Why diagram has been used in order to further dive into listed possibilities. As numerous possible causes were identified, a series of questions must be asked as to how they emerged and how they are affecting the company. The initial stage is succeeded by the validation of these initial causes. As the initial causes were validated or invalidated, the final causes were found to be the lack of assay quality checking procedures upon arrival from the supplier and stored products were exposed to temperatures exceeding the proper storage temperature specifications. As the final causes were discovered, alternative solutions must be designed per cause. An appropriate alternative must be chosen among the designed solutions using the Kepner-Tregoe Decision Analysis. A set of “musts” and “wants” agreed upon with the company will determine the viability of the solutions. To solve the lack of assay quality checking procedures upon arrival from the supplier and the stored products exposure to temperatures exceeding the proper storage specifications; implementation of selective assay testing procedures and good warehouse practices were the proposed solutions. Upon further evaluation of the solutions through a Potential Problem Analysis, contingency plans were formulated in order to ensure the smooth implementation of the solutions. A cost benefit analysis was conducted and reported that a sales opportunity benefit and cost reduction savings amounting to 119,200 PHP will be achieved by the proposed solutions. The three-month implementation which covers training, demonstration, application, and procedural analysis will allow the company to bridge the average product return gap between the 0.42% deviation from the 0.01% maximum tolerable limit.